Severity of the ductal shunt: a comparison of different markers. Issue 5 (19th August 2005) - El Hajjar, M; Vaksmann, G; Rakza, T; Kongolo, G; Storme, L
Abstract : Background: When the ductus arteriosus (DA) is patent, the ductal shunt is proportional to the ratio of left ventricular output (LVO) to systemic blood flow. Systemic blood flow can be estimated by measuring flow in the superior vena cava (SVC). Objective: To re-evaluate the accuracy of standard echocardiographic markers of patent ductus arteriosus (PDA) using LVO/SVC flow ratio. Methods: Prospective study. Preterm infants of 24–30 weeks gestational age and postnatal age less than 48 hours. The following echocardiographic criteria were measured: left atrial to aortic root ratio (LA/Ao); DA diameter by B mode and colour Doppler; mean and end diastolic flow velocity of the left pulmonary artery (LPA); LVO; SVC flow. Results: Twenty three preterm infants were enrolled (median gestational age 28 weeks (range 24–30), median birth weight 840 g (500–1440)). The DA was closed in eight (mean (SD) LVO/SVC 2.4 (0.3)) and open in 15 (mean (SD) LVO/SVC 4.5 (0.6)). An LA/Ao ratio ⩾1.4, a DA diameter ⩾1.4 mm/kg, and a mean and end diastolic flow velocity of LPA respectively ⩾0.42 and ⩾0.20 m/s identified an LVO/SVC ⩾4 with a sensitivity and a specificity above 90%. Conclusion: This study indicates that LA/Ao ratio, DA diameter, and mean and end diastolic flow velocity of the LPA are accurate markers of PDA. These standard echocardiographic variables are easy to measure and need less skill and resources than direct measurements of ductal shunt.